2000
DOI: 10.1021/la000736+
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-lysine)-g-poly(ethylene glycol) Layers on Metal Oxide Surfaces:  Surface-Analytical Characterization and Resistance to Serum and Fibrinogen Adsorption

Abstract: Poly(L-lysine)-g-poly(ethylene glycol) (PLL-g-PEG) is a member of a family of polycationic PEG-grafted copolymers that have been shown to chemisorb on anionic surfaces, including various metal oxide surfaces, providing a high degree of resistance to protein adsorption. PLL-g-PEG-modified surfaces are attractive for a variety of applications including sensor chips for bioaffinity assays and blood-contacting biomedical devices. The analytical and structural properties of PLL-g-PEG adlayers on niobium oxide (Nb2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
576
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 515 publications
(612 citation statements)
references
References 27 publications
32
576
0
4
Order By: Relevance
“…The N1s spectrum contained a NSi 3 contribution at 397.5 eV, but a shoulder corresponding to the NH 2 contribution at 399.3 eV, as reported by Bertoti, was not found. After PLL-g-PEG adsorption there is good agreement with the values of Huang et al [33] (referred to C1s at 284.6 eV). The O1s-Si peak overlaps with the NHC=O, [39].…”
Section: Xpssupporting
confidence: 87%
See 1 more Smart Citation
“…The N1s spectrum contained a NSi 3 contribution at 397.5 eV, but a shoulder corresponding to the NH 2 contribution at 399.3 eV, as reported by Bertoti, was not found. After PLL-g-PEG adsorption there is good agreement with the values of Huang et al [33] (referred to C1s at 284.6 eV). The O1s-Si peak overlaps with the NHC=O, [39].…”
Section: Xpssupporting
confidence: 87%
“…The C-Si component of the C1s peak shows a slight shift to 283.2 ± 0.03 eV. The C-C/C-H component is found at 285.6 ± 0.05 eV, which is 0.6 eV higher than the bare SiC value reported by Contarini et al [39] or the theoretical PLL-g-PEG value reported by Huang et al [33], and is shifted by about 1.6 eV from the value measured on bare SiC. Additionally, a C-O/C-N component at 287.2 ± 0.05 eV is shifted 1.4 eV from the measurement on bare SiC, and is around 0.7 eV higher than the theoretical value of the C-O component for PLL-g-PEG.…”
Section: Xpsmentioning
confidence: 56%
“…PLL-PEG was synthesized as in ref. 32 and adsorbed to glass coverslips (cleaned by sequential sonication in 3M KOH solution and ethanol) during a 15-min incubation as a 0.01-mg/mL solution in 10 mM K-Hepes (pH 7.8) buffer. Tetrahymena pellicles were a gift from Jan Brugues, MPI-CBG, Dresden, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial motility on the substrate was hindered by a poly͑L-lysine͒ coating of the glass slide, whereas the cantilever was functionalized with a layer of poly͑L-lysine͒-g-poly͑ethylene glycol͒ ͑PLL-g-PEG͒, a polymer known for its simplicity and effectiveness in resisting the absorption of biomolecules. 33 Figure 3͑b͒ shows five E. coli cells spatially displaced one after the other in order to be arranged along a virtual line.…”
Section: Force-controlled Spatial Manipulation Of Viable Mammalian Cementioning
confidence: 99%